Analysis Hubungan Perilaku Penggunaan APD Terhadap Terjadinya Kecelakaan Kerja di Pabrik Kelapa Sawit : Literatur Review - Nur Linda (Yayasan Daarul Huda Kruengmane, 2023)
The use of personal protective equipment has been regulated in Law no. 1 year 1970 concerning work safety and PER.08/MEN/VII/2010 concerning personal protective equipment. In this study, the design used is Literature Review. The method of searching for article data sources was carried out through the Google Scholar database in the 2019-2023 period to retrieve relevant articles published in Indonesian. The purpose of making the five journals is to find out the relationship between the use of PPE and the occurrence of work accidents. Furthermore, the method of the five journals above uses a cross sectional design. The instruments used in the five journals were partly a chi-square test and partly an analytic survey. Personal Protective Equipment (PPE) is a set of tools used by workers to protect part or all of their body from potential hazards or work accidents